CALLUS REGENERATION OF Chrysanthemum AFTER GAMMA RAY IRRADIATION FOR THE RESILIENCE OF MEDIUM PLAIN - Ari Wijayani; Muafi Muafi; Endah Wahyurini; Rina Sri Lestari (Universitas Pembangunan Nasional Veteran Yogayakarta, 2015)
Development of chrysanthemum plants in the medium plains is still facing obstacles due tounfavorable climate. Until today, the availability of tolerant chrysanthemum seeds grown in the mediumplains is not maximized so that the necessary effort in order to increase the genetic diversity as thematerial selection to obtain tolerant chrysanthemums grown in medium plain. This research is beingconducted in order to follow up the problems of availability of tolerant chrysanthemums seeds grown inthe medium plains at several stages. Stage one is the induction of callus after gamma ray irradiation invitro. This research has been conducted in tissue culture laboratory of the Faculty of Agriculture UPN